The digital palette of K azakhstan in the context of the study Tengrian internet communities - Temirbayeva, A.A.; Temirbayev, T.T.; Ryskiyeva, A.A.; Kuranbek, A.A. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
Scientific studies of interactions in the Internet space have been around for some time. The religious landscape of modern society is diverse; the scope of new technologies is constantly expanding. The Internet and new media have become widely used in the activities of social and religious movements. This is due to easy accessibility, cost-effectiveness, access to a wide audience, extraterritoriality, greater freedom from traditional forms of social control and authority, the ability to put forward alternative religious views, citizenship, create new communities, and even a new religion. Groups, communities, movements are being organized, including digital or online religions. Traditional and non-traditional religions have gradually become involved in the digitalization of religious life. The COVID 2019 pandemic has accelerated this process. During the lockdown period, religious associations began to conduct online worship, reading the Koran in an interactive mode. Tengrian groups, in turn, are also actively involved in the above media relations; they use the Internet and social networks for communication, interaction and dissemination of their views, active citizenship. Their own discourses arise, which correlate with the processes taking place in the country and in the world. In this regard, this article will consider the content analysis of Tengrian groups in social networks.
Тәңірлік интернет-қауымдастықтарды зерттеу контексіндегі Қазақстанның цифрлық палитрасы
Цифровая палитра Казахстана в контексте исследования тенгрианских Интернет-сообществ
Keywords: Digital religion; Tengri and the Internet; Tengri social networks; Digital Tengrism; Media space; Tengrians; Digitalization; Modern Tengrism; Tradition; Tengri online